2021
DOI: 10.1002/etc.5226
|View full text |Cite
|
Sign up to set email alerts
|

Changes in Sewage Sludge Chemical Signatures During a COVID‐19 Community Lockdown, Part 2: Nontargeted Analysis of Sludge and Evaluation with COVID‐19 Metrics

Abstract: Sewage sludge and wastewater include urine and feces from an entire community, and it is highly likely that this mixture contains chemicals whose presence is dependent on levels of SARS‐CoV‐2 in the community. We analyzed primary sewage sludge samples collected in New Haven, Connecticut, USA, during the initial wave of the COVID‐19 pandemic using liquid chromatography coupled with high‐resolution mass spectrometry and performed an exploratory investigation of correlations between chemical features and COVID‐19… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 34 publications
0
6
0
Order By: Relevance
“…The data described in the present study represent only a small fraction of what was collected using our high‐resolution MS methods. In part 2 of this series, we further investigate chemicals in the sludge that were not easily identifiable using our databases and examine chemical correlations with measured levels of SARS‐CoV‐2 RNA and other COVID‐19 metrics (Nason et al, 2021 ). Because both SARS‐CoV‐2 RNA analysis and liquid chromatography–high‐resolution MS analysis were conducted on the same samples, these complex analyses are an excellent opportunity to identify chemical signals that may provide information about COVID‐19 levels within the community.…”
Section: Resultsmentioning
confidence: 99%
“…The data described in the present study represent only a small fraction of what was collected using our high‐resolution MS methods. In part 2 of this series, we further investigate chemicals in the sludge that were not easily identifiable using our databases and examine chemical correlations with measured levels of SARS‐CoV‐2 RNA and other COVID‐19 metrics (Nason et al, 2021 ). Because both SARS‐CoV‐2 RNA analysis and liquid chromatography–high‐resolution MS analysis were conducted on the same samples, these complex analyses are an excellent opportunity to identify chemical signals that may provide information about COVID‐19 levels within the community.…”
Section: Resultsmentioning
confidence: 99%
“…About 60% of the world's population in 2017 had safe drinking water and cleanser for hand washing 18 . Multiple studies have found evidence of the existence of the COVID‐19 viral load in sewage out of an urban drainage system 19 . Other potential transmission routes include the release of untreated sewage into surface water (such as rivers) and the distribution of traditionally treated gray water as urban recycled water 9 .…”
Section: Water and Sustainable Developmentmentioning
confidence: 99%
“… 18 Multiple studies have found evidence of the existence of the COVID‐19 viral load in sewage out of an urban drainage system. 19 Other potential transmission routes include the release of untreated sewage into surface water (such as rivers) and the distribution of traditionally treated gray water as urban recycled water. 9 As a result of this unexpected and unusual event, there is a great deal of uncertainty about what will happen in the future, even though in a post‐COVID situation, the economy, agricultural production, and employment would be the main priorities for politicians.…”
Section: Water and Sustainable Developmentmentioning
confidence: 99%
“…Most studies investigating BOCs have used targeted analyses to identify the presence of specific pollutants. High-resolution mass spectrometry (HRMS)-based nontargeted and suspect screening analyses are alternative approaches to studying chemical contamination in environmental media. These methodologies are capable of detecting a broader range of analytes in a sample, including metabolites and environmental transformation products, compared to targeted analyses using lower-resolution MS instruments, and are increasingly being used to study chemical contamination of biosolids, including those produced in the U.S., Spain, Nigeria, France, Sweden, and the Arctic …”
Section: Introductionmentioning
confidence: 99%